The Cosmopolitan Turn: Recasting ‘Dialogue’ and ‘Difference’ - Strand, Torill (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2010)
This paper draws attention to the potential pitfalls and possibilities of a new cosmopolitanism. The first part of the paper briefly portrays cosmopolitanism as a name and metaphor for a way of life, an ideal and an outlook. The second part, however, discloses a paradoxical attribution of the metaphor, revealing the ways in which it assumes something which it is not. The third part of the paper further explores the powers of this paradox, arguing that the new cosmopolitanism can be seen as a riddle that surprises, bewilders and educates: The surprise is in the deviation from current and most common ways of speech. The bewilderment happens as the mantra of cosmopolitanism is bringing together logical opposites, jumbling categories and disturbing pre-existing modes of thought. The educational work of cosmopolitanism thus occurs as a violation of the cognitive framework and logical categories generating our very modes of learning. The vital work of the new cosmopolitanism is therefore in the ways in which it creates epistemic ruptures, recasts our mental categories, generates radically new modes of learning, and thus completely new ways of experiencing, seeing and knowing a world of change. But what are the potential pitfalls and possibilities of a discourse jeopardizing the very vision of the social world, and thus the world itself?